2015
DOI: 10.1038/jid.2014.409
|View full text |Cite
|
Sign up to set email alerts
|

Testing Chemotherapeutic Agents in the Feather Follicle Identifies a Selective Blockade of Cell Proliferation and a Key Role for Sonic Hedgehog Signaling in Chemotherapy-Induced Tissue Damage

Abstract: Chemotherapeutic agents induce complex tissue responses in vivo and damage normal organ functions. Here we use the feather follicle to investigate details of this damage response. We show that cyclophosphamide treatment, which causes chemotherapy-induced alopecia in mice and man, induces distinct defects in feather formation: feather branching is transiently and reversibly disrupted, thus leaving a morphological record of the impact of chemotherapeutic agents, whereas the rachis (feather axis) remains unpertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…This peculiar feature elegantly illustrates how chemotherapy damages the feather follicle: in the perturbed feathers, only the branched area showed reduced cell proliferation with concomitant reduction of Shh expression. The rachis region remained unperturbed (Figure G) . These results pinpoint a specific role of Shh signalling in chemotherapy‐induced tissue damage, which is further confirmed in the CIA mouse model .…”
Section: Conserved Role Of Shh Signalling In Vertebrate Epithelial Tisupporting
confidence: 69%
See 1 more Smart Citation
“…This peculiar feature elegantly illustrates how chemotherapy damages the feather follicle: in the perturbed feathers, only the branched area showed reduced cell proliferation with concomitant reduction of Shh expression. The rachis region remained unperturbed (Figure G) . These results pinpoint a specific role of Shh signalling in chemotherapy‐induced tissue damage, which is further confirmed in the CIA mouse model .…”
Section: Conserved Role Of Shh Signalling In Vertebrate Epithelial Tisupporting
confidence: 69%
“…These experimentally well‐supported, conventional concepts of CIA pathobiology became greatly enriched when the response of chicken feather follicles to chemotherapy was examined. This approach revealed that, unexpectedly, Shh signalling is also prominently involved in the follicular damage response . Although it is incompletely understood how specifically Shh signalling is involved, and what are the upstream events that inhibit Shh gene expression, the implication of this additional, important pathway represents a major step‐forward in CIA pathobiology, not the least since it invites novel CIA intervention strategies that had previously not been considered.…”
Section: Conserved Role Of Shh Signalling In Vertebrate Epithelial Timentioning
confidence: 99%
“…We found that WNT and hedgehog pathways fit this trend (Supplementary Table S3). Hedgehog signaling has been shown to be downregulated by cyclophosphamide in growing HFs (35). …”
Section: Resultsmentioning
confidence: 99%
“…A recent unique study addressed a cancer-related clinical issue by perturbing feather growth with chemotherapeutic agents (Xie et al, 2015). Cyclophosphamide (CYP) has been shown to cause chemotherapyinduced alopecia (CIA) in mice and humans.…”
Section: Eda Fn and Keloidsmentioning
confidence: 99%